Gambaran Kepatuhan Diet Hipertensi Pada Lansia Di Puskesmas Lakessi Kota Parepare - Nurul Fauziah; Martinus Jimung; Bahriah (Nursing Practice Journal, 2025)
Elderly people who have high blood pressure will experience an increase of more than half of the population aged 60 years with systolic pressure of 140 mmHg and diastolic 90 mmHg. Cardiovascular disease is the leading cause of death in the world, occurring at the age of 65 years and over with the most deaths in developing countries. The purpose of the study was to determine the description of hypertension diet compliance in the elderly at the Lakessi Health Center, Parepare City. The research method used in this study is quantitative descriptive with an instrument in the form of a questionnaire sheet. The subjects of the study were all elderly hypertensive patients as many as 53 elderly at the Lakessi Health Center, Parepare City in 2024 and families who accompanied the patients. The study results involved 53 elderly people, all of whom were compliant with the hypertension diet (100%). This means that 100% of respondents were compliant with the hypertension diet. The conclusion is that all respondents (53) were compliant in undergoing a hypertension diet because the level of awareness of the elderly is higher. Suggestions for further researchers to develop research with a more varied approach, such as a descriptive analytical design, in order to determine the relationship between variables such as education level, family support, or knowledge of the elderly with dietary compliance